2017
DOI: 10.1002/aur.1739
|View full text |Cite
|
Sign up to set email alerts
|

Infant muscle tone and childhood autistic traits: A longitudinal study in the general population

Abstract: Objective In a longitudinal population-based study of 2905 children, we investigated if infants’ neuromotor development was associated with autistic traits in childhood. Methods Overall motor development and muscle tone were examined by trained research assistants with an adapted version of Touwen’s Neurodevelopmental Examination between ages 2–5 months. Tone was assessed in several positions and items were scored as normal, low or high tone. Parents rated their children’s autistic traits with the Social Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 54 publications
1
31
0
1
Order By: Relevance
“…Many studies have reported co-occurrence of motor impairments with autistic traits and autism (6,7), and follow-up studies have shown early sensorimotor manifestations before an autism diagnosis in high-risk infants (8,9). We have previously shown that neuromotor development measured during infancy was associated with autistic traits in the current study population (10). Neuromotor development during infancy can be a measure of overall neurodevelopmental delay.…”
supporting
confidence: 46%
“…Many studies have reported co-occurrence of motor impairments with autistic traits and autism (6,7), and follow-up studies have shown early sensorimotor manifestations before an autism diagnosis in high-risk infants (8,9). We have previously shown that neuromotor development measured during infancy was associated with autistic traits in the current study population (10). Neuromotor development during infancy can be a measure of overall neurodevelopmental delay.…”
supporting
confidence: 46%
“…social, language, and repetitive behaviors) were measured by parental ratings using the scale 0 ( never true ) to 3 ( almost always true ), which we summed to yield a total SRS score. Serdarevic et al (2017) note that the SRS short-form correlated 0.95 with scores from the full SRS in a previous Dutch study.…”
Section: Methodsmentioning
confidence: 56%
“…ASD diagnosis. As reported by Serdarevic et al (2017), Generation R employed a multiple-gating procedure whereby children who (a) had a high score on the SRS short-form, (b) had a high score on the Social Communication Questionnaire (SCQ; Berument et al, 1999), or (c) had been assessed for ASD according to parental report were selected for a search of central medical records maintained by general practitioners. Only children for whom a diagnosis of ASD was confirmed by these medical records were considered ASD cases in this analysis.…”
Section: Srsmentioning
confidence: 99%
“…Physical activity (PA) is considered a protective factor in maintaining a healthy body weight and preventing obesity [58]. However, opportunities for PA may be limited in children with ASD due to social and behavioral challenges [59,60], as well as motor deficits [61,62,63].…”
Section: Physical Activity and Sedentary Behaviormentioning
confidence: 99%